Advanced automated software testing : frameworks for refined practice - Alsmadi, Izzat, 1972- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book discusses the current state of test automation practices, as it includes chapters related to software test automation and its validity and applicability in different domains"--Provided by publisher.
Keywords: Computer software -- Testing -- Automation.; elektronické knihy; electronic books